Situational Leadership Style : A Qualitative Study - Alhadi, Rus’an (Bulletin of Pedagogical Research, 2021)
This article aimed to describe Principal’s leadership and to describe about the leadership style. Because the leadership style of a principal can determine the success of all activities in the school including the learning process in the classroom. This leadership style would be reflected in how teachers carry out their basic duties as educators. With the qualitative method, the collective data used documentation and observation. The result showed Employee R1, leader S1. The leadership style in this scenario was top-down as R1 that associated with low skill as well as commitment. By directing and telling as clearly as possible what to do, leaders can control the outcome. Subordinates were also easier to complete the task. Employee R2, leader S2. Subordinates show a willingness to do tasks, but did not have enough skills. Thus, the leader was more in the role of supervisor or coach. Leaders can help subordinates gain experience and confidence. Employee R3, leader S3. In this scenario, subordinates already have skills and skills that were qualified but relatively low commitment. Therefore, the role of leaders was not to tell them what to do. Leaders were there to motivate and support to boost their confidence. Leaders also play a role in providing help and feedback on employee performance, but only when it's really needed. Employee S4, leader S4. Subordinates already have high skills supported with a high commitment to completing tasks. Therefore, the role of the leader was as a supervisor who monitors everything already goes according to plan. Keywords: Leadership Style, Situational Leadership Style, Principal’s Leadership